2019
DOI: 10.3389/fpsyg.2019.02155
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Reading Comprehension in Children With Cochlear Implants

Abstract: Children with a profound hearing loss who have been implanted with cochlear implants (CI), vary in terms of their language and reading skills. Some of these children have strong language skills and are proficient readers whereas others struggle with language and both the decoding and comprehension aspects of reading. Reading comprehension is dependent on a number of skills where decoding, spoken language comprehension and receptive vocabulary have been found to be the strongest predictors of performance. Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
14
0
3
Order By: Relevance
“…Concerning age at CI, Wass et al 45 found no association with parental university degree in Sweden, while Jeddi et al 22 found younger ages at CI with higher parental education in Iran.…”
Section: International: Sociological Factorsmentioning
confidence: 97%
“…Concerning age at CI, Wass et al 45 found no association with parental university degree in Sweden, while Jeddi et al 22 found younger ages at CI with higher parental education in Iran.…”
Section: International: Sociological Factorsmentioning
confidence: 97%
“…The delay in language acquisition in children with hearing loss later affects the learning process [ 3 ]. Receptive vocabulary is an important predictive factor in reading comprehension [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIn addition to the code-based skills such as PA and OK underlying reading, meaning-based skills (i.e., semantic competence) such as receptive vocabulary, quality of word representations, morphological awareness and listening comprehension are necessary to understand the decoded words, sentences and texts. For example, a number of studies found that large proportions of reading comprehension could be explained by variance in vocabulary once children with NH passed the early stages of reading development (Protopapas et al, 2007;Olson et al, 2011;Wass et al, 2019). Further, knowledge of word meaning contributed directly to reading comprehension (Ouellette and Beers, 2010;Perfetti and Stafura, 2014).…”
Section: Contribution Of Semantic Competence (Sc) To Reading In Children With Nh and Hlmentioning
confidence: 99%
“…TIn children with HL, meaning-based skills have also been found to play important roles in reading (Lederberg et al, 2014;Wass et al, 2019). For example, in alphabetic writing systems, Connor and Zwolan (2004) found that vocabulary growth had a positive effect on passage comprehension in primary and middle school children with CIs and Von Muenster and Baker (2014) reported strong correlations between receptive/expressive language skills and passage reading comprehension in children with CIs aged 5-13 years.…”
Section: Contribution Of Semantic Competence (Sc) To Reading In Children With Nh and Hlmentioning
confidence: 99%
See 1 more Smart Citation